Participant observation at a youth HIV conference. (March 2014) - Greifinger, Rena; St. Louis, Gemima; Lunstead, Julie; Malik, Neha; Vibbert, Martha
Young people living with HIV in the US have the potential to live long and healthy lives. However, the psychosocial impact of an HIV diagnosis, complicated by poverty, inequality, stigma and marginalization, create structural and behavioral challenges for young people that can overwhelm them and their health care providers. This narrative provides a reflective analysis of insights and discussions captured through participant observation at a five-day conference for young people living with HIV. The manuscript provides practitioners with an additional interpretive lens, highlighting participant observation as a valuable methodology to better understand and design programs for young people living with HIV. The article calls for youth-led, peer-based approaches that focus on support for disclosure of HIV status, self-esteem in relationships and adherence to medication.